Financial Strategies and Stock Return of Companies in Tehran Stock Exchange - Seyed Mohammad A'arabi (مطالعات مدیریت راهبردی, 2012)
Financial Strategies are Part of Corporate Strategy that are in Financial Management span and include decisions about Investment, Financing, Working Capital and Dividend. For evaluating and selection of these strategies, different inside and outside factors should be mentioned.  This article investigates the role of Strategic Reference Points Theory in making clear financial theories and strategies and analyzes the ways of using this theory for making strategic decisions in the field of financial affaires   in companies. The next point is that, coordination between these Strategies and Financial Strategy of a company (vertical alignment) and coordination between these strategies themselves (horizontal coordination) improve the performance. The findings approve the point.